Javanese Script Comic Strip "Si Kani": Character Education Learning Media of Serat Wulangreh Pupuh Kinanthi - Siti Nurjanah; Nur Hanifah Insani; Joko Sukoyo (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
Javanese script is a subject in Javanese language classes, which often perceived as complicated. This study aims to: 1) describe the findings from the needs analysis for developing Javanese script comic strip learning media at SMP Negeri 1 Jatibarang for Grade VIII, 2) develop a prototype of Javanese script comic strip media containing the content of Serat Wulangreh pupuh kinanthi, and 3) analyze the results of expert validation and student responses to the developed comic strip media. This study used Research and Development (R&D) development. The research model used the ADDIE (Analysis, Design, Development, Implementation & Evaluation) development model. The analysis technique in this study was quantitative data analysis and qualitative descriptive analysis with data collection techniques in the form of observation, interviews, and questionnaires. This study involved 32 eighth-grade students and Javanese language teachers at SMP Negeri 1 Jatibarang as research subjects. This study focused on the development of teaching materials in the form of Javanese script comic strips using Javanese script as the main font. The assessment results show that the media product is in the excellent category by material experts with a feasibility score of 98% and media experts with a score of 95%. Meanwhile, the teacher response results produced a feasibility score of 95% and the student response results with a score of 93.75% in the excellent category. These results show that these comic strips can be used effectively as an alternative medium for teaching materials.